Anti-aging composite insulator and preparation method thereof
By applying a composite coating on the insulator, combined with materials such as end hydroxyl polydimethylsiloxane, amino modified polymethylhydrogens, etc., the problem of RTV coating aging is solved, and the resistance to UV aging and soil resistance of the insulator is significantly improved.
Patent Information
- Application Number
- CN202411731907.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-07
AI Technical Summary
The existing RTV coatings are prone to aging during long-term operation of insulators, resulting in surface peeling, falling off and filth-depositing. How to improve its bonding strength with the insulator matrix and anti-aging and anti-fouling performance has become a hot topic of research.
The composite coating is used, consisting of terminal hydroxyl polydimethylsiloxane, amino modified polymethylhydrosiloxane, epoxy silane coupling agent, LaFeO3/TiO2 heterojunction nanoflowers and diluents. By improving film forming performance and binding strength, it improves anti-ultraviolet aging and anti-fouling properties.
It significantly improves the bonding strength of the composite coating and the alumina ceramic body, enhances the resistance to UV aging and stain resistance, and extends the service life of the insulator.
Smart Images

Figure CN119581153A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of insulation, in particular to an aging-resistant composite insulator and a preparation method thereof. Background Art
[0002] During the long-term operation of the power grid, insulators will be polluted by nature and a large amount of pollutants will accumulate on their surfaces. These pollutants will increase the weight of the insulators on the one hand, and reduce the flashover voltage of the insulators on the other hand, posing a hidden danger to the safe and stable operation of the power grid.
[0003] Preparing coatings on the surface of insulators is an important means to reduce the adhesion of pollutants, ensure the safe and stable operation of transmission lines, and reduce the maintenance cost of line operation. RTV coatings have good hydrophobicity, hydrophobic migration and recovery characteristics, and are often coated on the surface of insulators. However, as the operating time of insulators increases, RTV coatings gradually age, and problems such as surface peeling, shedding, and dirt deposition will occur. How to improve the bonding strength between RTV coatings and insulator substrates and improve their anti-aging and anti-fouling properties has become a current research hotspot. Summary of the invention
[0004] Purpose of the invention: In view of the above technical problems, the present invention proposes an aging-resistant composite insulator and a preparation method thereof.
[0005] The technical solutions adopted are as follows:
[0006] An aging-resistant composite insulator comprises an alumina ceramic body and a composite coating;
[0007] The composite coating is made of the following raw materials in parts by weight:
[0008] 60-80 parts of terminal hydroxyl polydimethylsiloxane, 5-10 parts of amino-modified polymethyl hydrogen siloxane, 1-3 parts of epoxy silane coupling agent, LaFeO 3 / TiO 2 5-10 parts of heterojunction nanoflowers, 0.01-0.1 parts of dibutyltin dilaurate, and 40-60 parts of diluent.
[0009] Furthermore, the preparation method of the amino-modified polymethyl hydrogen siloxane is as follows:
[0010] Add polymethylhydrogensiloxane and unsaturated amino compounds to toluene, use chloroplatinic acid as a catalyst, heat to reflux reaction for 10-20 hours, then return to room temperature, add water for extraction, collect the toluene phase, concentrate under reduced pressure, and then collect the product.
[0011] Furthermore, the unsaturated amino compound is any one of 2-aminomethyl methacrylate, 2-aminoethyl methacrylate, and 2-aminopropyl methacrylate, or a combination of two or more thereof.
[0012] Furthermore, the mass ratio of the polymethyl hydrogen siloxane to the unsaturated amino compound is 1-5:1-5.
[0013] Furthermore, the epoxy silane coupling agent is KH-560 and / or A-187.
[0014] Furthermore, the LaFeO 3 / TiO 2 The preparation method of heterojunction nanoflowers is as follows:
[0015] S1: Dissolve water-soluble lanthanum salt and water-soluble iron salt in deionized water, then dissolve citric acid, polyvinyl pyrrolidone and dodecyl carboxy betaine in anhydrous ethanol and add them, stir and mix, slowly drop the precipitant, seal the obtained mixed solution and heat it to 180-200℃ for solvent thermal reaction for 5-10h, return to room temperature after the reaction, collect the precipitate, wash and dry it to obtain LaFeO with flower-like structure 3 ;
[0016] S2: LaFeO 3 and titanium sulfate are dispersed in deionized water, and isopropanol is added and mixed. The obtained mixed solution is sealed and heated to 120-150°C for solvent thermal reaction for 10-20 hours. After the reaction is completed, the room temperature is restored, the precipitate is collected, washed and dried.
[0017] Furthermore, the precipitant is any one or a combination of two or more of sodium hydroxide aqueous solution, potassium hydroxide aqueous solution, and ammonia water.
[0018] Furthermore, the diluent is any one of turpentine, rosin water, toluene, xylene, ethyl acetate, and ethylene glycol ethyl ether, or a combination of two or more thereof.
[0019] The present invention also provides a method for preparing an aging-resistant composite insulator:
[0020] Hydroxyl-terminated polydimethylsiloxane, amino-modified polymethylhydrogensiloxane, epoxy silane coupling agent, LaFeO 3 / TiO 2 The heterojunction nanoflowers, dibutyltin dilaurate and diluent are uniformly mixed to obtain a composite coating. After the composite coating forms a film on the surface of the alumina ceramic body, the temperature is raised to 80-120° C. and dried for 1-10 hours.
[0021] Furthermore, the heating rate is 0.1-1°C / min.
[0022] Beneficial effects of the present invention:
[0023] The invention provides an aging-resistant composite insulator. Amino-modified polymethyl hydrogen siloxane contains long-chain alkoxy groups and amino side chains, has excellent lubricity and flexibility, and has good compatibility with terminal hydroxyl polydimethyl siloxane. After being added, the film-forming performance of the composite coating can be improved, and the bonding strength between the composite coating and the alumina ceramic blank can be improved. The epoxy silane coupling agent has a certain enrichment effect, and can migrate to the interface between the alumina ceramic blank and the composite coating to form hydrogen bonds, so that the bonding of the composite coating is more firm. Moreover, the epoxy group can also cross-link with the amino group to improve the density and adhesion of the composite coating. As the density of the composite coating increases, the ability to reflect and scatter ultraviolet rays is improved, thereby reducing the direct damage of ultraviolet rays to the composite coating and improving the anti-ultraviolet aging performance of the insulator.
[0024] LaFeO 3 / TiO 2 Heterojunction nanoflowers are constructed to form a heterostructure with a special microscopic morphology, which improves the separation efficiency of photogenerated carriers and overcomes the problem of TiO 2 The disadvantages of photocatalysts such as low quantum efficiency and inability to utilize visible light make it possible to effectively decompose organic matter under the irradiation of light with a wider range of wavelengths, thereby improving the anti-pollution ability of insulators. 2 It also has the function of shielding ultraviolet rays, and can improve the anti-ultraviolet aging performance of the composite coating.
[0025] The composite insulator prepared by the present invention has excellent anti-ultraviolet aging and anti-pollution properties and can be widely used in power transmission lines of my country's power system. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The LaFeO prepared in Example 1 3 / TiO 2 SEM image of heterojunction nanoflowers. DETAILED DESCRIPTION
[0027] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The techniques not mentioned in the present invention are all referenced to the prior art. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.
[0028] Embodiment 1:
[0029] An aging-resistant composite insulator comprises an alumina ceramic body and a composite coating;
[0030] The composite coating is made of the following raw materials in parts by weight:
[0031] 70 parts of terminal hydroxyl polydimethylsiloxane, 8 parts of amino-modified polymethyl hydrogensiloxane, 2 parts of KH-560, LaFeO 3 / TiO 2 8 parts of heterojunction nanoflowers, 0.05 parts of dibutyltin dilaurate, 50 parts of xylene, and 10 parts of ethyl acetate.
[0032] Wherein, the preparation method of amino-modified polymethyl hydrogen siloxane is as follows:
[0033] Under nitrogen protection, add 10g polymethylhydrogensiloxane (hydrogen content 1.2%) and 15.48g 2-aminoethyl methacrylate to 100ml toluene, add 0.001g chloroplatinic acid as a catalyst, heat to reflux and stir to react for 15h, then return to room temperature, add 100ml deionized water, stir and extract thoroughly, separate the toluene phase, dry it with anhydrous sodium sulfate, and concentrate it under reduced pressure.
[0034] LaFeO 3 / TiO 2 The preparation method of heterojunction nanoflowers is as follows:
[0035] 4.33 g La(NO 3 ) 3 6H 2 O, 4.04 g Fe(NO 3 ) 3 9H 2 O was dissolved in 100 ml of deionized water, and then 7.68 g of citric acid, 1 g of polyvinyl pyrrolidone and 1 g of dodecyl carboxy betaine were dissolved in 20 ml of anhydrous ethanol and added. After fully stirring to mix, ammonia water was slowly added dropwise to adjust the pH of the reaction system to 8. After the addition was completed, the obtained mixed solution was transferred to a high-pressure reactor with a polytetrafluoroethylene liner, sealed and heated to 180 ° C for solvent thermal reaction for 6 hours. After the reaction was completed, the room temperature was restored, and the precipitate was collected, fully washed with anhydrous ethanol and deionized water, and then dried to obtain LaFeO with a flower-like structure. 3 , take 2.43gLaFeO 3 Disperse 1.2g of titanium sulfate into 100ml of deionized water, add 10ml of isopropanol and mix well, then seal the obtained mixed solution and heat it to 140℃ for solvothermal reaction for 15h. After the reaction, return to room temperature, collect the precipitate, wash it thoroughly with anhydrous ethanol and deionized water, and then dry it.
[0036] Preparation method of the above-mentioned aging-resistant composite insulator:
[0037] Hydroxyl-terminated polydimethylsiloxane, amino-modified polymethylhydrogensiloxane, KH-560, LaFeO 3 / TiO 2The heterojunction nanoflowers, dibutyltin dilaurate, xylene and ethyl acetate are evenly mixed to obtain a composite coating. The cleaned alumina ceramic body is immersed in the composite coating for 30 seconds, and then the alumina ceramic body is slowly pulled upward. During this process, in order to ensure the uniformity of the composite coating, the alumina ceramic body keeps rotating, so that a layer of composite coating is formed on the alumina ceramic body, which is then placed in an oven and slowly heated to 100°C at a rate of 0.5°C / min and dried for 8 hours.
[0038] Embodiment 2:
[0039] An aging-resistant composite insulator comprises an alumina ceramic body and a composite coating;
[0040] The composite coating is made of the following raw materials in parts by weight:
[0041] 80 parts of terminal hydroxyl polydimethylsiloxane, 10 parts of amino-modified polymethyl hydrogen siloxane, 3 parts of KH-560, LaFeO 3 / TiO 2 10 parts of heterojunction nanoflowers, 0.1 parts of dibutyltin dilaurate, 50 parts of xylene, and 10 parts of ethyl acetate.
[0042] Among them, amino-modified polymethylhydrogensiloxane and LaFeO 3 / TiO 2 The preparation method of heterojunction nanoflowers is the same as that of Example 1;
[0043] Preparation method of the above-mentioned aging-resistant composite insulator:
[0044] Hydroxyl-terminated polydimethylsiloxane, amino-modified polymethylhydrogensiloxane, KH-560, LaFeO 3 / TiO 2 The heterojunction nanoflowers, dibutyltin dilaurate, xylene and ethyl acetate are evenly mixed to obtain a composite coating. The cleaned alumina ceramic body is immersed in the composite coating for 30 seconds, and then the alumina ceramic body is slowly pulled upward. During this process, in order to ensure the uniformity of the composite coating, the alumina ceramic body keeps rotating, so that a layer of composite coating is formed on the alumina ceramic body, which is then placed in an oven and slowly heated to 100°C at a rate of 0.5°C / min and dried for 8 hours.
[0045] Embodiment 3:
[0046] An aging-resistant composite insulator comprises an alumina ceramic body and a composite coating;
[0047] The composite coating is made of the following raw materials in parts by weight:
[0048] 60 parts of hydroxy-terminated polydimethylsiloxane, 5 parts of amino-modified polymethylhydrogensiloxane, 1 part of KH-560, LaFeO 3 / TiO 2 6 parts of heterojunction nanoflowers, 0.01 parts of dibutyltin dilaurate, 50 parts of xylene, and 10 parts of ethyl acetate.
[0049] Among them, amino-modified polymethylhydrogensiloxane and LaFeO 3 / TiO 2 The preparation method of heterojunction nanoflowers is the same as that of Example 1;
[0050] Preparation method of the above-mentioned aging-resistant composite insulator:
[0051] Hydroxyl-terminated polydimethylsiloxane, amino-modified polymethylhydrogensiloxane, KH-560, LaFeO 3 / TiO 2 The heterojunction nanoflowers, dibutyltin dilaurate, xylene and ethyl acetate are evenly mixed to obtain a composite coating. The cleaned alumina ceramic body is immersed in the composite coating for 30 seconds, and then the alumina ceramic body is slowly pulled upward. During this process, in order to ensure the uniformity of the composite coating, the alumina ceramic body keeps rotating, so that a layer of composite coating is formed on the alumina ceramic body, which is then placed in an oven and slowly heated to 100°C at a rate of 0.5°C / min and dried for 8 hours.
[0052] Embodiment 4:
[0053] An aging-resistant composite insulator comprises an alumina ceramic body and a composite coating;
[0054] The composite coating is made of the following raw materials in parts by weight:
[0055] 80 parts of terminal hydroxyl polydimethylsiloxane, 5 parts of amino-modified polymethyl hydrogen siloxane, 3 parts of KH-560, LaFeO 3 / TiO 2 8 parts of heterojunction nanoflowers, 0.1 parts of dibutyltin dilaurate, 50 parts of xylene, and 10 parts of ethyl acetate.
[0056] Among them, amino-modified polymethylhydrogensiloxane and LaFeO 3 / TiO 2 The preparation method of heterojunction nanoflowers is the same as that of Example 1;
[0057] Preparation method of the above-mentioned aging-resistant composite insulator:
[0058] Hydroxyl-terminated polydimethylsiloxane, amino-modified polymethylhydrogensiloxane, KH-560, LaFeO 3 / TiO 2The heterojunction nanoflowers, dibutyltin dilaurate, xylene and ethyl acetate are evenly mixed to obtain a composite coating. The cleaned alumina ceramic body is immersed in the composite coating for 30 seconds, and then the alumina ceramic body is slowly pulled upward. During this process, in order to ensure the uniformity of the composite coating, the alumina ceramic body keeps rotating, so that a layer of composite coating is formed on the alumina ceramic body, which is then placed in an oven and slowly heated to 100°C at a rate of 0.5°C / min and dried for 8 hours.
[0059] Comparative Example 1:
[0060] The process is substantially the same as Example 1, except that KH-560 is not added.
[0061] Comparative Example 2:
[0062] The method is basically the same as Example 1, except that the same mass of polymethyl hydrogen siloxane is directly added to replace the amino-modified polymethyl hydrogen siloxane.
[0063] Comparative Example 3:
[0064] The method is basically the same as Example 1, except that amino-modified polymethyl hydrogen siloxane is not added.
[0065] Comparative Example 4:
[0066] The same as Example 1, except that nano-TiO 2 Replace LaFeO 3 / TiO 2 Heterojunction nanoflowers.
[0067] Performance Test:
[0068] The performance of the composite coatings in Examples 1-4 and Comparative Examples 1-4 was tested;
[0069] ① Test the adhesion of the composite coating after the composite coating is cured in accordance with GB / T 9286-1998. Use a grid knife to scratch the composite coating 6 times in the horizontal and vertical directions. Then use 3M tape to completely adhere to the scratched area. Within 5 minutes, quickly tear off the tape at a 60° angle to the coating. The entire tearing time is controlled within 0.5-1s. After tearing off, evaluate the adhesion level;
[0070] ② The composite coating was coated on an alumina ceramic plate with a size of 25.4×76.2 mm, with a coating amount of 1 g. The alumina ceramic plate was then placed in an oven and slowly heated to 100°C at a rate of 0.5°C / min for 8 hours. The plate was taken out and added to 100 ml of methyl orange solution (40 mg / L) for photocatalytic degradation experiments. A high-pressure mercury lamp was used to simulate visible light, and the visible light intensity at the surface of the solution was 10 mW / cm 2, after 120 minutes of degradation, 5 ml of sample was taken, and its absorbance was measured by UV-visible spectrophotometer to analyze the change of methyl orange concentration, and then the photocatalytic degradation rate was calculated according to the change of absorbance;
[0071] The UV-1140 ultraviolet accelerated weathering test chamber was used to simulate the aging effect of ultraviolet rays in sunlight on the composite coating. The test chamber used a UVA-340 fluorescent ultraviolet lamp as the ultraviolet light source with an irradiation intensity of 0.68W / m 2 (340nm), which is equivalent to the average sunlight intensity at noon in summer at the equator. Referring to the UV aging test standard, when the test chamber is operated at 65-70℃, 12h of indoor UV radiation is equivalent to 30d of outdoor UV radiation. The aging time is set to 288h, and the composite coating is tested in ① and ② respectively. The test results are shown in Table 1 below:
[0072] Table 1:
[0073]
[0074] As can be seen from Table 1 above, the composite coating of the present invention has extremely strong adhesion to the substrate and excellent self-cleaning ability;
[0075] From the comparison between Example 1 and Comparative Examples 1-3, it can be seen that the addition of KH-560 and amino-modified polymethylhydrogensiloxane plays a positive role in improving the adhesion strength of the composite coating and improving the anti-ultraviolet aging ability. Due to the aging of the composite coating, the color of the composite coating becomes darker, cracks appear inside, and LaFeO 3 / TiO 2 The heterojunction nanoflowers peel off, and the light absorption capacity decreases, thus leading to a decrease in the photocatalytic degradation efficiency;
[0076] From the comparison between Example 1 and Comparative Example 4, it can be seen that compared with nano-TiO 2 , LaFeO 3 / TiO 2 Heterojunction nanoflowers have higher photocatalytic activity, which can significantly improve the self-cleaning ability of the composite coating.
[0077] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. An aging-resistant composite insulator, characterized in that: It includes an alumina ceramic body and a composite coating; The composite coating is made of the following raw materials in parts by weight: 60-80 parts of terminal hydroxyl polydimethylsiloxane, 5-10 parts of amino-modified polymethyl hydrogen siloxane, 1-3 parts of epoxy silane coupling agent, 5-10 parts of LaFeO3 / TiO2 heterojunction nanoflowers, 0.01-0.1 parts of dibutyltin dilaurate, and 40-60 parts of diluent.
2. The aging-resistant composite insulator according to claim 1, characterized in that: The preparation method of the amino-modified polymethyl hydrogen siloxane is as follows: Add polymethylhydrogensiloxane and unsaturated amino compounds to toluene, use chloroplatinic acid as a catalyst, heat to reflux reaction for 10-20 hours, then return to room temperature, add water for extraction, collect the toluene phase, concentrate under reduced pressure, and then collect the product.
3. The aging-resistant composite insulator according to claim 2, characterized in that: The unsaturated amino compound is any one of 2-aminomethyl methacrylate, 2-aminoethyl methacrylate, and 2-aminopropyl methacrylate, or a combination of two or more thereof.
4. The aging-resistant composite insulator according to claim 2, characterized in that: The mass ratio of the polymethyl hydrogen siloxane to the unsaturated amino compound is 1-5:1-5.
5. The aging-resistant composite insulator according to claim 1, characterized in that: The epoxy silane coupling agent is KH-560 and / or A-187.
6. The aging-resistant composite insulator according to claim 1, characterized in that: The preparation method of the LaFeO3 / TiO2 heterojunction nanoflower is as follows: S1: Dissolve water-soluble lanthanum salt and water-soluble iron salt in deionized water, then dissolve citric acid, polyvinyl pyrrolidone and dodecyl carboxy betaine in anhydrous ethanol and add them, stir and mix, slowly drop the precipitant, seal the obtained mixed solution and heat it to 180-200℃ for solvent thermal reaction for 5-10h, return to room temperature after the reaction, collect the precipitate, wash and dry to obtain LaFeO3 with flower-like structure; S2: Disperse LaFeO3 and titanium sulfate in deionized water, add isopropanol and mix well, seal the obtained mixed solution and heat it to 120-150℃ for solvothermal reaction for 10-20h, return to room temperature after the reaction, collect the precipitate, wash and dry it.
7. The aging-resistant composite insulator according to claim 6, characterized in that: The precipitant is any one of sodium hydroxide aqueous solution, potassium hydroxide aqueous solution and ammonia water, or a combination of two or more thereof.
8. The aging-resistant composite insulator according to claim 1, characterized in that: The diluent is any one of turpentine, rosin water, toluene, xylene, ethyl acetate, and ethylene glycol ether, or a combination of two or more thereof.
9. A method for preparing an aging-resistant composite insulator according to any one of claims 1 to 8, characterized in that: The terminal hydroxyl polydimethylsiloxane, amino-modified polymethylhydrogensiloxane, epoxy silane coupling agent, LaFeO3 / TiO2 heterojunction nanoflowers, dibutyltin dilaurate and diluent are uniformly mixed to obtain a composite coating. After the composite coating forms a film on the surface of the alumina ceramic body, the temperature is raised to 80-120°C and dried for 1-10 hours.
10. The method for preparing an aging-resistant composite insulator according to claim 9, characterized in that: The heating rate is 0.1-1℃ / min.